Long term perspectives in evaluation : increasing relevance and utility - Forss, Kim; Lindkvist, Ida; McGillivray, Mark (New York, NY : Routledge, 2021)
"Long Term Perspectives in Evaluation is the first book to advocate the virtues of a long-term perspective for policy evaluation as well as to show how evaluations can take a longer time perspective than they usually do. To get there, it is necessary to understand the decision-making context of evaluations and study the obstacles and the resistance towards long-term perspectives - as knowledge of that will lay the ground for more effective advocacy. The book is divided into three parts: Part One examines different aspects of methodology and methods. In Part Two, authors present case studies of long-term evaluations, examine their own experiences of such evaluations and discuss difficulties, challenges, and lessons learned. Cases discussed include: education sector reforms in Sweden, local governance reforms in Denmark, policy interventions in southern Italy and Brazil and Paris declaration principles of aid effectiveness such as Swedish aid to Tanzania, Vietnam, Laos and Sri Lanka. Finally Part Three sees authors turns to a set of contextual issues and concluding remarks. Bringing together a rich collection of insights and a renowned group of experts, Long Term Perspectives in Evaluation: Increasing Relevance and Utility, constitutes a significant landmark in the field"--
Foreword / Patricia Rogers -- Introduction / Kim Forss and Ida Lindkvist -- Historians' debates on time and the nature of historical research / Charlotta Forss -- Counting the long-term in evaluation / Jens Andersson -- Contribution analysis and the long-term perspective : challenges and opportunities / John Mayne -- Using a wide lens to take a long view : how integrating systems thinking into evaluations can assist in taking a long-term perspective / Andrew Koleros -- Reforms of local governments in Denmark / Olaf Rieper -- Reform takes time, but politics won't wait : the scope for long-term evaluation in the education sector / Rolf Sandahl and Gustav Jakob Petersson -- Looking from a local place to take the long view in evaluation / Laura Tagle -- Complex development aid evaluations : the aid quality evaluation framework / Mark McGillivray and David Carpenter -- Why take a long view? : how formal and informal rules influence the choice of time perspectives in international development evaluations / Alison Pollard and Ida Lindkvist -- Long-term causal inference / Markus Palenberg -- From measuring impact to understanding change / Kim Forss -- Concluding remarks on evaluating the long-term : it works but can be made to work better! / Ida Lindkvist, Kim Forss & Mark McGillivray.
OCLC-licensed vendor bibliographic record.
Keywords: Policy sciences -- Evaluation; Evaluation research (Social action programs); POLITICAL SCIENCE / Public Policy / General; POLITICAL SCIENCE / Government / General